EFEKTIVITAS KEBIJAKAN BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM MENINGKATKAN KINERJA SEKOLAH - Simanjuntak, Robet Januar; Suriansyah, Ahmad; Purwanti, Ratna (STKIP Pesisir Selatan, 2025)
This study aims to analyze the effectiveness of the School Operational Assistance (BOS) policy in improving school performance, particularly in terms of financial management, the quality of learning, and school governance. BOS is a strategic government program designed to support the delivery of equitable and quality basic education services. In its implementation, BOS funds are used to finance routine school operational needs and to enhance student participation and learning outcomes. The method used in this study is descriptive qualitative, employing literature review and field observation approaches. The findings indicate that the implementation of the BOS policy generally has a positive impact on improving school performance, especially in the provision of educational infrastructure, teacher professionalism development, and improved access to quality learning. However, the effectiveness of this program is highly influenced by the management capacity of schools, transparency in financial reporting, and the involvement of stakeholders such as school committees and the community. Therefore, strengthening governance, continuous supervision, and technical training in BOS fund management are key to optimizing the implementation of the BOS program in order to achieve better educational quality outcomes.